Logan Medallist 3. Making Stratigraphy Respectable: From Stamp Collecting to Astronomical Calibration - Miall, Andrew (Geoscience Canada, 2015)
The modern science of stratigraphy is founded on a nineteenth- century empirical base – the lithostratigraphy and biostratigraphy of basin-fill successions. This stratigraphic record comprises the most complete data set available for reconstructing the tectonic and climatic history of Earth. However, it has taken two hundred years of evolution of concepts and methods for the science to evolve from what Ernest Rutherford scornfully termed “stamp collecting” to a modern dynamic science characterized by an array of refined methods for documenting geological rates and processes. Major developments in the evolution of the science of stratigraphy include the growth of an ever-more precise geological time scale, the birth of sedimentology and basin-analysis methods, the influence of plate tectonics and, most importantly, the development, since the late 1970s, of the concepts of sequence stratigraphy. Refinements in these concepts have required the integration of all pre-existing data and methods into a modern, multidisciplinary approach, as exemplified by the current drive to apply the retrodicted history of Earth’s orbital behaviour to the construction of a high-precision ‘astrochronological’ time scale back to at least the Mesozoic record. At its core, stratigraphy, like much of geology, is a fieldbased science. The field context of a stratigraphic sample or succession remains the most important starting point for any advanced mapping, analytical or modeling work.